Penyusunan Enterprise Architecture Planning (EAP) Menggunakan TOGAF Pada PT. Pelabuhan Indonesia III (persero) - Ony Prabowo; Tan Amelia; Yoppy Mirza Maulana (Jurnal Sistem Informasi Universitas Dinamika, 2015)
PT. Pelabuhan Indonesia III (Persero) or PT. Pelindo III is a State-Owned Enterprise engaged in the sector transportation. Duties, powers and responsibilities of this company is to manage the public ports in seven provinces in Indonesia. PT. Pelindo III has a vision